The influence of product attribute, promotion mix, distribution channel, and price toward repurchase intention on iPhone - Hadi, Antonius Satria (Asian Management and Business Review, 2021)
The purpose of this research is to examine the effect of product attribute on repurchase intention, the effect of promotion mix on repurchase intention, the influence of distribution channel on repurchase intention, and the effect of price on repurchase intention, both partially and simultaneously. Respondents in this study were 99 students from several universities in Yogyakarta. The analytical technique used in this research is multiple linear regression analysis, F test and t test. All tests using IBM SPSS software version 23. The results of this study prove that product attribute has a positive effect on repurchase intention, price has a positive effect on repurchase intention, and promotion mix has a positive effect on repurchase intention. Each of hypotheses discussed in detail into this article.